Profiles of binding sites to lectin and custom-made neoglycoprotein probes in liver of developing duck embryos - Jacinto, Sonia Donaldo; Kayser, Klaus; Gabius, Hans-Joachim (Philippines Rushing Water Publishers, 1995)
"The possible roles played by lectin and lectin binding sites in liver development of duck embryos were initially investigated by looking at the interaction between lectin probes and receptor sites in embryotic liver. Binding patterns to the lectins VAA, UDA, and 14 kD, the fucan fucoidan and neoglycoproteins- BSA conjugated to glucNAc, B-galNAc, fucose, mannose, maltose and lactose were monitored in liver of duck embryos. Embryos were studied with at most 10 specimens observed for days 1, 3, 5, 8, 10, 13 and 17 of incubation. Of the probes used receptors for UDA, fucoidan and the neoglycoptroteins maltose-BSA and B-galNAc-BSA showed trends of developmental regulation. Maltose and UDA, B-galNAc and UDA, maltose and B-galNAc as well as fucoidan and B-galNAc and fucoidan and UDA binding are strongly to moderately coexpressed in the periods of observation. Fucoidan was strongly to weakly coexpressed with maltose."
Keywords: Ducks; Ligandhistochemistry; Neoglycoproteins; Binding sites; Hepatocytes developmental regulation